The mapping of love and death : a Maisie Dobbs novel - Winspear, Jacqueline, 1955- (Winspear, Jacqueline, 1955- Maisie Dobbs novel., 2010)
"Maisie Dobbs must unravel a case of wartime love and death--an investigation that leads her to a doomed affair between a young cartographer and a mysterious nurse"--Provided by publisher.